FAMILY SUPPORT FOR DIETARY COMPLIANCE IN GOUTY ARTHRITIS PATIENTS - Siti Khoiriyah SK; Sri Mulyani SM; Ardiana A (Fakultas Ilmu Kesehatan (FIKES) Universitas Sains Al-Qur'an (UNSIQ) Jawa Tengah di Wonosobo, 2025)
Gourt arthritis is a mertabolic diseraser caurserd by a burildurp of purriners, eritherr durer to increraserd produrction or ther kidnerys bering urnabler to erxcrerter therm so that urric acid crystals accurmurlater in ther joints. Ther inciderncer of gourt is arournd 1-4% of ther gernerral popurlation, in wersterrn courntriers mern surfferr from gourt at a higherr rater than womern at 3-6%. In somer courntriers, prervalerncer can increraser to 10% in mern and 6% in womern in ther ager ranger ≥80 yerars. Gourty arthritis surfferrerrs nererd to gert family surpport in ther procerss of controlling therir diert so that urric acid lerverls in ther body can ber controllerd therrerby rerdurcing ther nurmberr of illnerssers. Ther aim of this rerserarch is to derterrminer ther rerlationship bertwerern family surpport and diertary compliancer in gourty arthritis surfferrerrs in ther working arera of ​​ther Jurmo Purblic Heralth Cernterr, Termanggurng Rergerncy. Research methods: Ther rerserarch dersign urserd was derscriptiver analytical correrlation with a cross serctional approach. Ther nurmberr of samplers in ther sturdy was 42 rerspondernts with a sampling terchniqurer ursing purrposiver sampling. Results: Data analysis urserd ther chi squrarer terst to derterrminer ther rerlationship bertwerern family surpport and diertary compliancer in gourty arthritis surfferrerrs. Ther rersurlts of data analysis obtainerd p-valurer = 0.001 (p<0.05). Conclursion: Therrer is a rerlationship bertwerern family surpport and diertary compliancer in gourty arthritis surfferrerrs in ther Jurmo Termanggurng heralth cernterr working arera